Media Effects Across Time and Subject: How News Coverage Affects Two Out of Four Attributes of Consumer Confidence - Boukes, Mark; Damstra, Alyt; Vliegenthart, Rens (Communication research, 2021)
Previous studies using aggregate-level designs demonstrated that the tone of economic news affects consumer confidence. However, the individual-level mechanisms underlying this effect remain to be investigated: It is not clear which consumer confidence attributes are most susceptible to media effects. Theoretically, we integrate the economic voting literature and extend media system dependency by differentiating between the media effects on sociotropic versus egocentric evaluations and the effects on prospective versus retrospective economic evaluations. Methodologically, data from a manual content analysis are linked to data from a three-wave panel survey, containing repeated measurements of consumer confidence. The findings demonstrate that the effects of tone on consumer confidence are largely a consequence of media effects on its sociotropic and prospective attributes: As citizens were exposed to relatively more positive economic news, only the national economic evaluations and expectations for the future improved. The egocentric and retrospective evaluations were not influenced by the tone in news that people had been exposed to.